Growth And Characterization Of Indium Oxide Nanostructured Films Using Solid-to-vapor Deposition Technique For Photoelectrochemical Applications - Moses, Aper Terwase (2022)
This research investigates the morphological, structural, optical, and photoelectrochemical properties of In2O3 nanostructured films synthesized on Si(100) and Ni/Si(100) substrates using the chemical vapor deposition technique at atmospheric pressure under hydrogen reducing ambient, and carbothermal reduction, respectively. The properties of the synthesized films were studied under several growth conditions such as; temperature, gas flow rates, and post-annealing under ammonia ambient. Analysis revealed changes in the surface morphology of the films with variations in growth conditions. EDX measurements showed non-stoichiometric in all the films with an In/O atomic ratio above the stoichiometric value of 0.667, which indicates oxygen deficiency. XRD analysis confirmed the formation of highly crystalline indium oxide nanostructures of the body-centered cubic (bcc) crystal structure with predominate growth in the (222) plane. Samples optical bandgap variation with growth conditions was also observed from analysis of reflectance data. Annealing under ammonia ambient resulted in the formation of N-doped In2O3 nanostructured materials. The photoelectrochemical study performed in a 0.5 M KOH solution revealed an onset potential of 0.72 (V vs. Ag/AgCl) for photoanodic current in the electrodes fabricated under hydrogen reducing ambient with the most efficient photoanode (fabricated at 950 oC), generating a maximum photocurrent density of 2.56 (mA/cm2)